ANALISIS KEMAMPUAN EMPATI GURU BK DALAM MELAKSANAKAN LAYANAN KONSELING INDIVIDUAL DI MAN 3 LANGKAT - Dewi Sinta; Zuraida Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the empathy skills of Guidance and Counselling (BK) teachers in providing individual counselling services at MAN 3 Langkat. Empathy is an important competency that guidance and counselling teachers must possess because it plays a role in building a warm, safe, and trusting counselling relationship, making students feel comfortable in expressing their problems. This research uses a quantitative approach with a descriptive method. The research subjects consisted of all Guidance and Counselling teachers at MAN 3 Langkat as observation respondents and a number of students who had previously received individual counselling services as questionnaire respondents. Data collection techniques were carried out thru distributing questionnaires to students and direct observation of the implementation of individual counselling services by guidance counselors. The data obtained were analyzed using descriptive statistics with categorization into high, medium, and low categories. The research results show that the empathy ability of guidance counselors based on student questionnaires is in the medium category, and the results of direct observation also indicate that the empathy ability of guidance counselors is in the medium category. These findings indicate that guidance counselors have been able to demonstrate empathetic attitudes in individual counselling services, such as understanding students' feelings, showing care, controlling emotions, and providing appropriate and non-judgmental responses, although implementation still needs improvement so that empathy can be felt more optimally by all students. Thus, it can be concluded that the empathy ability of Guidance and Counselling teachers at MAN 3 Langkat is quite good in the implementation of individual counselling services.